Konsep Pendekatan Behavior dalam Menangani Perilaku Indisipliner pada Siswa Korban Perceraian - Wahyudi, Muchamad Agus Slamet (Universitas Islam Negeri Raden Intan Lampung, 2017)
This research implies the concept of behavioral approach in dealing with in disciplinary behavior in students of divorce victims. Behavior itself is one of the guidance in guidance and counseling to overcome maladaptive behavior toward adaptive. Behavioral approach is the right approach to handle undisciplined students in school. So that students are able to perform their duties well in school, without experiencing obstacles. This undisciplined behavior is influenced by one of the factors of internal student problems, which tend to be from a student's background due to a divorce. The research method using qualitative descriptive approach by emphasizing on direct plunge. Furthermore, if the assessment has been done, then the planning can be implemented to the counseling process. Started contract counseling, relaxation, modeling, reward and punishment until the follow-up phase.